APLIKASI PENGAMANAN BASIS DATA MENGGUNAKAN ALGORITMA XXTEA - Raden Sangunda Marga (2021)
Theft of data derived from database backups can be a loophole in data security. These loopholes can be avoided by securing using cryptography on data backup files. So unauthorized parties cannot exploit loopholes to misuse data. The method that the author uses in this final task is the encryption method using the XXTEA Algorithm. Encryption is the name of a process where it scrambles the data contained in a file or message. So it is difficult to know the contents of the data if you do not know the specific password. The XXTEA algorithm is a symmetric cryptographic algorithm that uses the same key to perform encryption and decryption processes. This research resulted in an application utilizing XXTEA algorithm and PHP 7.3 programming language. Hasil trial that the author did, generated in the form of a file with sql format that has been encrypted and has a key. The database file can be decrypted by using the same key in the encryption process.